A model-based measurement device in European fiscal policy-making: The ontology and epistemology of potential output - Jakob Kapeller; Philipp Heimberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
While the development of scientific theories and measurement concepts has always been strongly intertwined, model-based measurements, specified as parameters in a statistical model, have been receiving increasing attention over the last decades. In this paper, we analyze the ontological and epistemological characteristics of such a model-based measurement device in an economics context. Specifically, our analysis focuses on the European Commission's model for estimating 'potential output' and 'natural unemployment', which is employed to facilitate the coordination of fiscal policies across the European Union. We find that the model's estimates strongly reflect the ontological and epistemological preconceptions underlying its design. Thereby, we point to a series of decisive differences in the realms of engineering and economics when it comes to the actual implementation of measurement techniques as well as the application and interpretation of measurement outcomes.
Keywords: 330; measurement theory; model-based measurement; economic models; economic policy; Kalman filter; European Union.